Longitudinal relationship between problematic internet use with loneliness during and after COVID-19 social restrictions - Phil Reed (Psychiatry Research, 2023)
Two, three-month long longitudinal studies examined the temporal relationships between problematic internet use (PIU), internet usage, and loneliness ratings, during and after lockdown restrictions. Experiment 1 examined 32, 18-51 year old participants, over a three-month period of lockdown restrictions. Experiment 2 studied 41, 18-51 year old participants, over a three-month period following the lifting of lockdown restrictions. Participants completed the internet addiction test, UCLA loneliness scale, and answered questioned about their online usage, at two time points. All cross-sectional analyses revealed a positive relationship between PIU and loneliness. However, there was no association between online use and loneliness. Longitudinal relationships between PIU and loneliness differed during and after lockdown restrictions. During a period of lockdown, there were both positive associations between earlier PIU and subsequent loneliness, and between earlier loneliness and subsequent PIU. However, following the easing of lockdown restrictions, only the temporal relationship between earlier internet addiction and later loneliness was significant.